Imagens urbanas: diálogos entre moda, sujeito e cidade (ModaPalavra e-periódico, 2010)
This essay discusses some issues related to the Streetwear’s universe, according to the media logic, looking for relations that could be established – from the Fashion, the Communication, the subjects and the streets. The discussion, beginner and promising, part of a research project in development, is based on the reading and observation of some photographs published on the blog of Scott Schuman, TheSartorialist, being selected from among a whole range of media products that have the Streetwear in the focus of your interest.
Keywords: Streetwear; Media; Representation of the subject